Pre-diabetes and cardiovascular risk factors in NAFLD patients: a retrospective comparative analysis - Teimouri, Azam; Ebrahimpour, Zahra; Feizi, Awat; Iraj, Bijan; Saffari, Elahe; Akbari, Mojtaba; Karimifar, Mozhgan (Frontiers in Endocrinology, 2025)
ObjectivesInsulin resistance plays a critical role in the pathophysiology of diabetes mellitus and non-alcoholic fatty liver disease (NAFLD). Moreover, insulin resistance has a central role in atherogensis as the major leading cause of cardiovascular disease (CVD). The aim of the present study was to assess the frequency of pre-diabetes and evaluate the cardiometabolic risk factors among NAFLD patients, comparing those with pre-diabetes to those with normal glucose tolerance.MethodsIn the current retrospective case-control study, the data of 1031 NAFLD patients was retrieved. Based on blood glucose levels, 337 diabetics, 340 pre-diabetes, and, 354 normal glucose patients were diagnosed. After excluding diabetic NAFLD patients, 694 individuals were divided into two groups: normal glucose and pre-diabetes. Various variables, such as age, anthropometric measurements, hypertension, systolic and diastolic blood pressure, and lipid profiles, were extracted from patient files. Statistical analysis was conducted to assess cardiovascular risk factors in NAFLD patients.ResultsHigher age, female gender, higher BMI, triglyceride, waist and hip circumference and waist-to-hip ratio were found in pre-diabetic NAFLD individuals compared with normoglycemic ones (P-value<0.05). Multivariable age-, sex-, BMI- and smoking- adjusted logistic regression showed a predicting role of pre-diabetes and NAFLD concurrence with metabolic syndrome (P-value<0.001, OR:4.31, 95% CI: 2.95- 6.29), but not CVD (P-value=0.353, OR:1.37, 95% CI: 0.71- 2.61).ConclusionIn this study, nearly one-third of NAFLD patients had pre-diabetes. The mean value of age, BMI, TG, waist and Hip circumference was significantly higher in pre-diabetic patients. The concurrence of pre-diabetes and NAFLD was a predicting factor for metabolic syndrome, but not CVD events.